Glyme-Lithium Bis(trifluoromethylsulfonyl)amide Super-concentrated Electrolytes: Salt Addition to Solvate Ionic Liquids Lowers Ionicity but Liberates Lithium Ions. Issue 9 (13th September 2021) - Kitada, Atsushi; Koujin, Yoshiki; Shimizu, Masahiro; Kawata, Kio; Yoshinaka, Chiaki; Saimura, Masayuki; Nagata, Takashi; Katahira, Masato; Fukami, Kazuhiro; Murase, Kuniaki
Abstract : Solvate ionic liquids (ILs) such as binary equimolar mixtures of glymes (ethyleneglycol-dimethylether or CH3 (OCH2 CH2 ) n OCH3 ) and lithium bis(trifluoromethylsulfonyl)amide (LiTf2 N; Tf = SO2 CF3 ) are known to show identical self-diffusion coefficients for glymes and Li + ions. Here, we report that the addition of LiTf2 N to the solvate ILs drastically changes their electrolyte properties. When the lithium salts are added to give the super-concentrated electrolytes with [O]/[Li + ] = 3 (molar ratio of ether oxygen to Li + ), ligand exchange or hopping conduction of Li + takes place for triglyme (G3; n = 3) and tetraglyme (G4; n = 4). In addition, the Li + transference number t Li+(EC), electrochemically measured under anion blocking conditions, increases about 3–6 times compared with the solvate ILs. Consequently, segmental motion of glymes apparently affects the transport properties even for the shorter G3 in the super-concentrated region. The relationship between the coordination structure and the transport properties are also discussed as a function of ionicity, the extent of the contribution of self-diffusion to the actual ion conduction. Plots vs ionicity demonstrate that a clear line can be drawn between the solvate ILs and the super-concentrated electrolytes.